Motivational Teaching Strategies in EFL Writing Class: Insights from Lecturer Perceptions - Nurul Fachrunnisa; Kisman Salija; Sahril Nur (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
The implementation of motivational strategies not only promotes a positive attitude towards writing but also encourages more effective development of students’ writing skills. This study explores lecturers’ insights on how they perceive the motivational teaching strategies in their English writing class. This study employs a qualitative approach with two English writing lecturers from Maros Muslim University as participants. Semi-structured interviews and classroom observation were the instruments used to collect the data and the data were analyzed using thematic analysis. The results show that both lecturers implement motivational strategies effectively by utilizing positive reinforcement, active learning strategies, and addressing students’ difficulties. Positive reinforcement significantly improves students’ motivation and writing performance. It was strengthened by the observational data that showed both lecturers constantly praised students whenever they responded positively during learning process. Lecturers emphasize that giving active learning strategies can motivate students to engage actively in writing tasks, which can enhance motivation and writing proficiency. The lecturers also acknowledge that addressing students’ difficulties is essential in reducing their anxiety and fostering confidence in writing. Recognizing and responding to students’ difficulties can reduce anxiety and encourage them to share their thoughts more confidently in writing.